Insights into Severe 5, 10‐Methylenetetrahydrofolate Reductase Deficiency: Molecular Genetic and Enzymatic Characterization of 76 Patients. Issue 6 (27th April 2015) - Burda, Patricie; Schäfer, Alexandra; Suormala, Terttu; Rummel, Till; Bürer, Céline; Heuberger, Dorothea; Frapolli, Michele; Giunta, Cecilia; Sokolová, Jitka; Vlášková, Hana; Kožich, Viktor; Koch, Hans Georg; et al.
<x xml:space="preserve">Abstract</x> We investigated molecular and biochemical defects in fibroblasts from 76 patients with severe MTHFR deficiency, the most common inherited disorder of folate metabolism. There is a good correlation between the type and location of defect at the DNA level with the manner and severity of biochemical disruption, findings which have implications for disease diagnosis and, potentially, treatment.